Effects of optimism on motivation in rats - Rygula, Rafal; Golebiowska, Joanna; Kregiel, Jakub; Kubik, Jakub; Popik, Piotr (Frontiers in Behavioral Neuroscience, 2015)
In humans, optimism is a cognitive construct related to motivation; optimists exert effort, whereas pessimists disengage from effort. In this study, using a recently developed ambiguous-cue interpretation (ACI) paradigm we took the unique opportunity to investigate whether ‘optimism’ as a trait is correlated with motivation in rodents. In a series of ACI tests (cognitive bias screening, CBS), we identified rats displaying ‘pessimistic’ and ‘optimistic’ traits. Subsequently, we investigated the trait differences in the motivation of these rats to gain reward and to avoid punishment using a progressive ratio schedule of reinforcement paradigm. Although ‘optimistic’ and ‘pessimistic’ animals did not differ in their motivation to avoid punishment, the ‘optimistic’ rats were significantly more motivated to gain reward than their ‘pessimistic’ conspecifics. For the first time, we showed an association between cognitive judgment bias and motivation in an animal model. Because both investigated processes are closely related to mental health and wellbeing, our results may be valuable for preclinical modeling of many psychiatric disorders.